Dual anterior descending coronary artery associated with coronary artery disease - Siqueira,Luciane da L. V. (2003)
The patient is a male with risk factors for coronary artery disease, who was referred for cardiac catheterization after acute myocardial infarction in the inferior wall. The patient underwent transluminal coronary angioplasty in the right coronary artery with successful stent implantation.